Detection of ERBB2 (HER2) Gene Amplification Events in Cell-Free DNA and Response to Anti-HER2 Agents in a Large Asian Cancer Patient Cohort - Lee, Jeeyun; Franovic, Aleksandra; Shiotsu, Yukimasa; Kim, Seung Tae; Kim, Kyoung-Mee; Banks, Kimberly C.; Raymond, Victoria M.; Lanman, Richard B. (Frontiers in Oncology, 2019)
Background: HER2 antagonists have marked activity and are approved for the treatment of HER2 overexpressing breast and gastric cancers. Recent studies have shown that ERBB2 (HER2) gene amplification and overexpression may also be actionable in other tumor types. Inter- and intratumoral heterogeneity in HER2 status, however, poses a significant challenge in identifying patients that may benefit from HER2-targeted therapies. ERBB2 amplification as identified by circulating cell-free DNA (cfDNA), which circumvents tissue heterogeneity issues, is emerging as a robust biomarker predictive of response to anti-HER2 agents. Here, the prevalence and genomic landscape of ERBB2 alterations detectable by next-generation sequencing (NGS) of cfDNA was evaluated in a large cohort of Asian patients with advanced solid tumors. Methods: Results were queried for consecutive patients (n = 469) tested by a comprehensive 70/73-gene cfDNA NGS assay (Guardant360®) between November 2015 and June 2018. Patients with ERBB2 gene alterations including copy number amplifications (CNAs), single nucleotide variants (SNVs), and insertion-deletions (indels) were identified. Results:ERBB2 alterations were detected in 52 patients (11.1%); ERBB2 SNVs, CNAs, and indels were found in 27 (5.8%), 27 (5.8%), and 10 (2.1%) patients, respectively. ERBB2 amplification was most frequently identified in gastric (21.4%; 6/28), colorectal (11.1%; 5/45), lung (3.9%; 9/231), and breast (3.2%; 1/31) cancer patients. ERBB2 amplification was often mutually exclusive with other oncogenic alterations in gastric (83.3%; 5/6) and colorectal (60%; 3/5) cancer patients. ERBB2 copy number gains were also highest in gastric and colorectal cancers (median 4.8 and 6.6, respectively). We further report two cases of advanced gastric cancer patients, one treatment naïve, and the other having failed four lines of therapy, whose ERBB2 CNAs were identified by cfDNA and derived clinical benefit from HER2-based therapies. Conclusion: Our data indicate that ERBB2 amplification is a common event in solid tumors among Asian cancer patients. High ERBB2 incidence and copy number gains were observed in gastric and colorectal cancer patients, often in the absence of other oncogenic mutations, underscoring its likely role as the driver alteration in those settings. Finally, we show the potential of comprehensive cfDNA testing in identifying patients who are most likely to benefit from HER2-targeted therapies.